Bibliometric Analysis of The Mawlid Celebration - Chasan, Muchammad Ikfil; Rakhmadi, Triyono; Basit, Abdul (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Mawlid is celebrated by Muslims around the world. Despite its popularity, there is no data regarding how this popularity portrayed in scientific research. This article aims to present a bibliometric overview related to research on mawlid over 25 years. This article can also be a guide for researchers interested in the Mawlid theme, so that they can obtain information about what journals to consult when they want to know more about mawlid. This article uses the Scopus Database to collect Mawlid-related articles. The data were further analyzed to find several bibliometric indicators. This article found that English is the most used language (48 documents). Anthropology is the most popular research area (15 documents). In 3 decades, from 1997 to 2022, Mawlid’s research has increased. From the beginning there was one document in the 90s, it increased to 9 documents in the 2001s, and in the last decade, it has increased to 47 documents. The country with the most publications is the UK (17 documents). The journals Cumhuriyet Ilahiyat Dergisi and Studia Islamika are the two publishers with the most publications of Mawlid Article. The most influential author was S. Schielke (2 documents and 34 citations). This article shows that although research publications related to Mawlid celebration have been found since 1997, but its popularity have increased over the past ten years.